The Impacts of Pelosika and Ameroro Dams in the Flood Control Performance of Konaweha River - Arif Sidik (Journal of the Civil Engineering Forum, 2016)
Konaweeha watershed is the largest watershed in Southeast Sulawesi with Konaweeha River as the main river. The main issues in Konaweeha Watershed is floods that occur caused damage to infrastructure and public facilities, lowering agricultural production, and cause fatalities. One of the government's efforts to cope with the flooding problem in Konaweeha Watershed is planning the construction of multi-purpose dams in the upstream of Konaweeha Watershed that is Pelosika Dam and Ameroso Dam. Necessary to study the flood control performance of the two dams. Analyses were performed with hydrologic-hydraulic modeling using HEC-HMS software (Hydrologic Modelling System) version 4.0 and HEC-RAS (River Analysis System) version 4.1. The design rainfalls that were used as input to the model were 2 year, 5-year, 10-year and 25 year. Scenarios used in this study are: (1) Existing Scenario (2) Pelosika Dam Scenario; (3) Ameroro Dam Scenario; (4) Pelosika and Ameroro Dams Scenario. The results showed the maximum water surface elevation along the downstream of Konaweeha River in Scenario (2) and (4) were almost the same in the 2 and 5 years return period design flood. However, in case of 10 and 25 years return period, the difference of maximum water surface elevation at downstream of Konaweeha River was slightly significant. Furthermore, the damping efficiency of the peak discharge (at Probably Maximum Flood or PMF) was found to be 71.70% and 18.18% for the individual Pelosika Dam and Ameroro Dam respectively. Further discussion suggests the development of Pelosika Dam as the higher priority rather than that of the Ameroro Dam.